Tracking the emergence of a pitch hierarchy using an artificial grammar requires extended exposure - Sauvé, Sarah A.; Satkunarajah, Praveena; Zendel, Benjamin Rich (Frontiers in Cognition, 2023)
The tonal hierarchy is a perceived musical structure implicitly learned through exposure. Previous studies have demonstrated that new grammars, for example based on the Bohlen-Pierce scale, can be learned in as quickly as 20 minutes. In this study, we create two grammars derived from the Bohlen-Pierce scale similar in complexity to the western tonal hierarchy. Participants rated the goodness-of-fit of all Bohlen-Pierce scale notes in a probe tone paradigm before and after 30 minutes of exposure to one of the two grammars. Participants were then asked about their experience in a short interview. Results do not support the learning of the artificial grammar: correlations between goodness-of-fit ratings and pitch frequency distribution of a grammar were no different before and after exposure to a grammar. Interviews suggest that participants are bad at identifying the strategy they used to complete the task. Testing the strategies reported on the data revealed that ratings decreased with increasing distance of the probe tone from the tonic. This is consistent with early brain responses to chromatic pitches of the tonal hierarchy. We suggest that longer exposure time is necessary to learn more complex grammars.